Modafinil improves methamphetamine-induced object recognition deficits and restores prefrontal cortex ERK signaling in mice - Gonzalez, Betina (2014)
Chronic use of methamphetamine (METH) leads to long-lasting cognitive dysfunction in humans and in animal models. Modafinil is a wake-promoting compound approved for the treatment of sleeping disorders. It is also prescribed off label to treat METH dependence. In the present study, we investigated whether modafinil could improve cognitive deficits induced by sub-chronic METH treatment in mice by measuring visual retention in a Novel Object Recognition (NOR) task. After sub-chronic METH treatment (1 mg/kg, once a day for 7 days), mice performed the NOR task, which consisted of habituation to the object recognition arena (5 min a day, 3 consecutive days), training session (2 equal objects, 10 min, day 4), and a retention session (1 novel object, 5 min, day 5). One hour before the training session, mice were given a single dose of modafinil (30 or 90 mg/kg). METH-treated mice showed impairments in visual memory retention, evidenced by equal preference of familiar and novel objects during the retention session. The lower dose of modafinil (30 mg/kg) had no effect on visual retention scores in METH-treated mice, while the higher dose (90 mg/kg) rescued visual memory retention to control values. We also measured extracellular signal-regulated kinase (ERK) phosphorylation in medial prefrontal cortex (mPFC), hippocampus, and nucleus accumbens (NAc) of METH- and vehicle-treated mice that received modafinil 1 h before exposure to novel objects in the training session, compared to mice placed in the arena without objects. Elevated ERK phosphorylation was found in the mPFC of vehicle-treated mice, but not in METH-treated mice, exposed to objects. The lower dose of modafinil had no effect on ERK phosphorylation in METH-treated mice, while 90 mg/kg modafinil treatment restored the ERK phosphorylation induced by novelty in METH-treated mice to values comparable to controls. We found neither a novelty nor treatment effect on ERK phosphorylation in hippocampus or NAc of vehicle- and METH-treated mice receiving acute 90 mg/kg modafinil treatment. Our results showed a palliative role of modafinil against METH-induced visual cognitive impairments, possibly by normalizing ERK signaling pathways in mPFC. Modafinil may be a valuable pharmacological tool for the treatment of cognitive deficits observed in human METH abusers as well as in other neuropsychiatric conditions.